A novel inorganic–organic nanohybrid material H4SiW12O40/pyridino-MCM-41 as efficient catalyst for the preparation of 1-amidoalkyl-2-naphthols under solvent-free conditions. Issue 20 (28th May 2015) - Tayebee, R.; Amini, M. M.; Akbari, M.; Aliakbari, A.
<x xml:space="preserve">Abstract</x> A new inorganic–organic nanohybrid material was prepared and performed as an efficient catalyst for the one-pot multi-component synthesis of different substituted 1-amidoalkyl-2-naphthols under solvent-free conditions.